Location, Location, Location - David Schwab, PhD (Blackwell Synergy, 2000)
There is an old saying that if you are buying a house, there are 3 factors to consider: location, location, and location. The same advice holds true for prosthodontists who are establishing new practices, moving their established practice, or opening a satellite office.